ANALYSIS OF WORD FORMATION PROCESS IN ONLINE SHOP’S TERMINOLOGIES - Tira Nur Fitria (Universitas Muhammadiyah Surakarta, 2022)
This study is to analyzes the type of word formation process of terms in online shops. Thisresearch used descriptive qualitative. The result of the analysis shows four types of wordformation process in online shops, namely derivation, compounding, clipping, and acronym.The derivation is the process of forming words by giving affixes to the word, so results in newword formation causes a change in word-class and its meaning. The examples of suffix are -er,-or, -al, -ment, -ed, –ing in the words “Seller, Buyer, Supplier, Retailer, Counter, Hanger,Customer, Testimonial, Endorsement, Payment, Booked, Trusted, Shipping, Booking,Packaging”. The examples of the prefix is re- in the words “Return, Refund, Restock,Refurbish”. Compounding is the process of forming words by combining two or more classesof words into a new form such as in the words “Handmade, Dropship, Download, Upload,Cashback, Online, Offline, Stockroom, Showroom, Giveaway, Fullset, Checkout”. Clipping is theprocess of forming words by cutting parts of the word itself or forming words from words thathave more than one syllable that gets the word cutting process at the beginning or end such asin the words “Advertisement (Ad), Original (Ori), Brother (Bro), Sister (Sist)”. The acronym isthe process of formation by taking from the initial letter in each syllable arranged to mentionthe abbreviation or extension of a term, so the result can be pronounced as a word. Forexample in the words “COD (Cash on Delivery), PO (Pre Order), DP (Down Payment), FP (FullPayment), PL (Price List), (PM) Private Message, IDR (Indonesian Rupiahs), WTB (Want toBuy), WTS (Want to Sell), WS (WholeSale), ATC (Add to Chart), RC (Recommended Seller).Keywords: word-formation, word-formation process, online shop, terms, morphology